Tasydid dalam Tilawah Al Quran dengan Langgam Jawa M. Yaser Arafat : Analisis Fonetik Akustik dan Temuan Penelitian - Ar Romli, Fikri Bahruddin; Rahman, Abdul; Mulyaningsih, Dede (UPT Publikasi Ilmiah, 2024)
This article is a study of the reading of the Javanese version of the Koran as an object of study in researching the reading or pronunciation of tasydid readings as one of the studies of acoustic phonetics within the scope of ashwat (phonology). The recitation sample was taken from a video reading of the qori, M. Yaser Arafat on May 15 2015, who recited the Koran with a Macapat rhythm. The researcher described and measured the duration of the tasydid and explained the duration of the qari's reading of the tasydid by referring to the science of tajwid using a descriptive-contrastive acoustic phonetic approach. Data is taken from readings containing tasydid. The data is transcribed and then identified in a table and measured using the timer feature. This study revealed that the duration for each tasydid category varies. For the mad 2 harakat group, it ranges from 0.4 to 0.8 seconds, while for the mad 2/4/6 harakat group, it spans from 0.7 to 2.7 seconds. The duration for the mad 4-5 harakat group falls between 1.3 and 2 seconds. Factors impacting these durations include variations in phonetic systems, reading style preferences, and adherence to Tajwid rules.